Plyometric training improves some physical and biomotoric parameters of young male basketball players - Cigerc, A. E.; Genc, H. (International Journal of Applied Exercise Physiology, 2020)
Plyometric training is essential for basketball players as well as for every athlete. Although the effect of plyometric training on players is very well researched, some deficiencies especially about anaerobic power parameter are noticeable. The target of current study was to demonstrate the effect of 8-week plyometric training applied to male basketball players aged 15-16 on some anthropometric and performance-based parameters. Volunteers were seperated two groups asplyometric training group (PTG) and control group (CG). PTG was applied plyometric training during 8 weeks and 3 days per week additionally basketball training. CG just continued basketball training. The effect of plyometric training was compared after eight weeks with repeated measures MANOVA for the tests. While there was a significant difference in height and body weight on behalf of PTG, a statistically significant improvement was found in all performance measurements except star excursion balance test (SEBT), running-based anaerobic sprint test (RAST) minimum power and fatigue index parameters of PTG. The results indicate that plyometric training is very effective in terms of physical and biomotoric features of young basketball players.